GCM2 mutation in primary hyperparathyroidism - A Case Report - Zuzanna Chmielowiec; Magdalena Pach; Natalia Wierzejska; Agnieszka Fugas; Karolina Smykiewicz; Aneta Michalczewska; Agnieszka Nowak; Alicja Partyka; Mariola Dziedzic; Justyna Dobrzańska (Kazimierz Wielki University, 2024)
Primary hyperparathyroidism is a common endocrine disorder. It is characterised by elevated parathyroid hormone (PTH) level causing hypercalcemia. 90-95% of cases have a spontaneous cause, with the remaining 5-10% having a genetic basis. On routine examination, a 47-year-old patient was found to have hypercalcemia, vitamin D deficiency, normal PTH levels and no hypercalciuria. Despite vitamin supplementation, calcemia remained unchanged. Single photon emission computed tomography (SPECT) examination detected possible adenomas in the lower parathyroids regions, and ultrasound revealed an adenoma of the lower left parathyroid gland and hypertrophy of the lower right parathyroid gland. The atypical clinical presentation - young age, inadequate normal PTH levels and the location of the lesions within the two parathyroid glands suggested genetic testing, which confirmed the presence of a genetic mutation - the GCM2 variant. Treatment included exploration of the parathyroid area using fluorescence. Both lower parathyroid glands were dissected. PTH monitoring showed a decrease in baseline levels of more than 50% after surgery. One month after surgery, PTH and calcium levels remained normal. Primary hyperparathyroidism is usually asymptomatic, detected when laboratory tests are performed for another cause. Symptoms include nephrolithiasis, bone and joint pain, osteoporosis, arrhythmias and fatigue. The typical patient has high PTH levels and hypercalcemia, but not every case will be schematic. High serum calcium levels do not always result in increased PTH levels and an in-depth diagnosis is required. The GCM2 mutation, detected in the patient presented here, may occur in familial isolated hyperparathyroidism. Correct diagnosis and treatment is crucial not only for the patient, as it significantly improves their quality of life, but also for their family members, who may also have a genetic mutation and be unaware of the disorder developing in their body.